The problems of innovative activity activization - Vetsepura, N.; Prokofieva, S. (Економічний вісник Донбасу, 2016)
Methods of innovation activization have been considered in the article with the purpose of ensuring the competitiveness of the economy of Ukraine. The state of innovation development of industrial production in Ukraine and the Donetsk region have been analyzed. The determinative value of labor factor in the innovation organization has been showed. У статті розглянуто способи активізації інноваційної діяльності з метою забезпечення конкурентоспроможності економіки України. Проаналізовано стан інноваційного розвитку промислового виробництва в Україні та Донецькій області. Показано визначальне значення людського фактора в організації інновацій. В статье рассмотрены способы активизации инновационной деятельности с целью обеспечения конкурентоспособности экономики Украины. Проанализировано состояние инновационного развития промышленного производства в Украине и Донецкой области. Показано определяющее значение человеческого фактора в организации инноваций.